1995
DOI: 10.1007/bf00051586
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of thidiazuron and benzyladenine in axillary shoot formation depends on sequence of application in Miscanthus X ogiformis ?Giganteus?

Abstract: Shoots of Miscanthus X ogiformis Honda 'Giganteus' transferred from medium with benzyladenine (BA) to thidiazuron (TDZ) formed significantly more axillary shoots than shoots grown continuously on either medium, or transferred from TDZ to BA. Shoot formation on axillary shoots transferred from BA-containing media to media with kinetin or isopentenyladenine (2iP) or transferred from media with TDZ, kinetin or 2iP to media with BA, corresponded to the number of shoots formed in the previous subculture. Shoot form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 23 publications
1
16
0
2
Order By: Relevance
“…In order to identify cytokinin receptor(s), numerous cytokinin-binding proteins (CBPs) were characterized (Brault et al 1999). Based on an analogy to the animal hormone system, Nielsen et al (1995) proposed a model for cytokinin action in plant cells. Both BA and TDZ can bind to a receptor of cytokinin binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify cytokinin receptor(s), numerous cytokinin-binding proteins (CBPs) were characterized (Brault et al 1999). Based on an analogy to the animal hormone system, Nielsen et al (1995) proposed a model for cytokinin action in plant cells. Both BA and TDZ can bind to a receptor of cytokinin binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…They found that explants obtained from 7-day-old seedlings cultured on MS medium containing BA in combination with TDZ (2 mg l −1 each) produced a higher number of shoots than with either cytokinin alone. A model was proposed by Nielsen et al (1995) for cytokinin action in the plant cell. Both BA and TDZ can bind to a receptor, a cytokinin-binding protein (CBP) which has two binding sites.…”
Section: Involvement Of Plant Growth Regulatorsmentioning
confidence: 99%
“…In vitro propagation of M. Â giganteus has been conducted by shoot regeneration from axillary nodes and apical meristems followed by in vitro tillering (Nielsen et al, 1993;Nielsen et al, 1995;Lewandowski, 1997), and by plantlet regeneration through somatic embryogenesis of callus induced from shoot apices, leaf sections and immature inflorescence tissues (Holme & Petersen, 1996;Lewandowski, 1997). Previous investigations have focused on optimization of tissue culture conditions to improve the induction rate of the embryogenic callus type, described as a compact opaque white callus, by addition of proline and different carbon sources, and the use of suspension culture methods in M. Â giganteus (Holme et al, 1997;Petersen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%